2015
DOI: 10.1002/mnfr.201500304
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of dietary hydroxytyrosol acetate, an extra virgin olive oil polyphenol in murine collagen-induced arthritis

Abstract: HTy-Ac improved the oxidative events and returned pro-inflammatory proteins expression to basal levels probably through JAK/STAT, MAPKs and NF-κB pathways. HTy-Ac supplement might provide a basis for developing a new dietary strategy for the prevention of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 52 publications
9
41
0
Order By: Relevance
“…In this sense, defective T‐cell pathway signaling occurs in SLE and it has been directly implicated in causing epigenetic abnormalities that result in lupus‐like autoimmunity . Moreover, different studies have shown that EVOO and some EVOO bioactive components are able to modulate ERK phosphorylation in different inflammatory model s , including pristane‐induced SLE in mice . In our study, we found that ERK phosphorylation was significantly increased after PHA stimulation compared with nonstimulated cells in patients with SLE and healthy donors.…”
Section: Discussionsupporting
confidence: 49%
“…In this sense, defective T‐cell pathway signaling occurs in SLE and it has been directly implicated in causing epigenetic abnormalities that result in lupus‐like autoimmunity . Moreover, different studies have shown that EVOO and some EVOO bioactive components are able to modulate ERK phosphorylation in different inflammatory model s , including pristane‐induced SLE in mice . In our study, we found that ERK phosphorylation was significantly increased after PHA stimulation compared with nonstimulated cells in patients with SLE and healthy donors.…”
Section: Discussionsupporting
confidence: 49%
“…At the hepatic level, activated PPAR‐α enhances lipolysis, mitochondrial β‐oxidation of FAs, and TAG storage, while reducing lipogenesis . Although PPAR‐α activation is accomplished by FAs such as docosahexaenoic acid (DHA; C22:6 n‐3), there is no clear evidence showing this property for EVOO, a product that is capable of upregulating Nrf‐2 signaling in other experimental models . According to these backgrounds, the aim of this work was to test the influence of a combination of low doses of DHA and EVOO supplementation on the activation level of transcription factors PPAR‐α, Nrf2, NF‐κB, and SREBP‐1c, in relation to the attenuation of liver (i) steatosis, (ii) pro‐inflammation, (iii) oxidative stress, (iv) pro‐lipogenic status, and (v) preservation of n‐3 long‐chain PUFAs (LCPUFA) content altered in HFD‐fed mice.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in an experimental collagen-induced arthritis (CIA) mice arthritis model, extra-virgin olive-oil polyphenol extract containing hydroxytyrosol was proven to exert anti-inflammatory and joint-protective effects. When given at the doses of 100 and 200 mg/kg/day, these extracts reduced the levels of proinflammatory mediators (TNF-α, IFN-γ, IL-1 β, IL-6, IL-17 A, and PGE2) [26] and decreased serum IgG1 and IgG2a, cartilage olimeric matrix protein (COMP), and metalloproteinase-3 (MMP-3) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our results nicely fit with literature data for rheumatoid arthritis models. Hydroxytyrosol acetate (HTy-Ac) is able to lower the activation of the Janus kinase-signal transducer and activator of transcription (JAK/STAT), mitogen-activated protein kinases (MAPKs), and nuclear transcription factor-kappa B (NF-κB) pathways and thus to downregulate the arthritic process in CIA mice [26,27]. In human fibroblast-like synoviocytes (FLSs) derived from arthritic tissues, resveratrol inhibits COX-2/PGE2 expression and reduces p65 phosphorylation [29].…”
Section: Discussionmentioning
confidence: 99%